Education for Sustainable Development as Strategy for Climate Change Adaptation and Mitigation: A Literature Review - Donna Lou E. Neri (Philippine Association of Institutions for Research, Inc., 2012)
The World Health Organization (2003) stated that there is growing evidence that changes in the global climate will have profound effects on the well-being of citizens in countries throughout the world. The "business as usual" frame of mind in dealing with this phenomenon is no longer feasible. Rather, there is a great need for a "sense of urgency" to empower and actively involve every individual to adapt and to mitigate the worsening of climate change. A great number of studies show that the leadership of the educational system in developed countries for more than 2 decades has been successful in promoting environmental sustainability. Some of these studies are reviewed and documented in this paper so that vulnerable countries may learn and benchmark from their experiences.